Determinasi Financial Technology Dengan Pendekatan Unified Theory of Acceptance and Use of Technology II - Amir Hamzah; Nurfania Sukma (Faculty of Economic and Business, 2021)
Currently, human life is in the era of globalization where in carrying out human activities, it is inseparable from the use of technology. One of the fields that are experiencing developmental with current technological advances is the financial sector. Which is often referred to as financial technology, which cannot be separated from innovation and acceptance of fintech itself. This study aims to examine and analyze the determination of financial technology with the UTAUT II approach. This study uses primary data from questionnaires to 176 respondents. The analytical method used is Structural Equation Model (SEM). The results showed that variables performance expectancy, effort expectancy, social influence, facilitating conditions, price value, perceived risk had a positive effect on behavioral intention. Hedonic motivation, habit had no effect on behavioral intention, and behavioral intention had a positive effect on use behavior. The results of this study can provide empirical evidence related to the analysis of the financial technology determination to the UTAUT II approach. This research also provide policy input, which is a solution to research problems regarding the use of interest and the behavior of using financial technology in Kuningan Regency.Cara Mengutip:Hamzah, A., & Sukma, N. (2021). Determinasi Financial Technology Dengan Pendekatan Unified Theory of Acceptance and Use of Technology II. Esensi: Jurnal Bisnis dan Manajemen, 11(1), xx-xx. https://doi.org/10.15408/ess.v11i1.19155.